1981
DOI: 10.1080/10862968109547413
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility in the Use of Graphic and Contextual Information by Good and Poor Readers

Abstract: Abstract. Two studies are reported that investigate the use of graphic and contextual information in word recognition. Subjects orally read stories that contained ten words that were altered by substituting a single letter, so that another word was formed that was anomalous within the sentence. The critical dependent variable was the proportion of times the subject read the contextually appropriate word rather than the actual stimulus word. The first study used different orienting instructions to manipulate su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…When skilled and less-skilled readers are reading materials of comparable difficulty (an important control, see Stanovich, 1986) the reliance on contextual information relative to graphic information is just as greatin many cases greaterfor the less-skilled readers (Allington and Fleming, 1978;Biemiller, 1970Biemiller, , 1979Harding, 1984;Juel, 1980;Lesgold, Resnick, and Hammond, 1985;Leu, DeGroff, and Simons, 1986;Nicholson and Hill, 1985;Nicholson, Lillas, and Rzoska, 1988;Perfetti and Roth, 1981 ;Richardson, DiBenedetto, and Adler, 1982;Simons and Leu, 1987;Whaley and Kibby, 1981). The results from studies of text disruption effects, timed text reading, and a variety of other paradigms also display a similar pattern (Allington and Strange, 1977;Biemiller, 1977Biemiller, -1978Ehrlich, 1981;Lovett, 1986;Nicholson, 1991;Schwartz and Stanovich, 1981;Stanovich, Cunningham, and Feeman, 1984;Strange, 1979).…”
Section: The Role Of Context In Word Recognitionmentioning
confidence: 75%
“…When skilled and less-skilled readers are reading materials of comparable difficulty (an important control, see Stanovich, 1986) the reliance on contextual information relative to graphic information is just as greatin many cases greaterfor the less-skilled readers (Allington and Fleming, 1978;Biemiller, 1970Biemiller, , 1979Harding, 1984;Juel, 1980;Lesgold, Resnick, and Hammond, 1985;Leu, DeGroff, and Simons, 1986;Nicholson and Hill, 1985;Nicholson, Lillas, and Rzoska, 1988;Perfetti and Roth, 1981 ;Richardson, DiBenedetto, and Adler, 1982;Simons and Leu, 1987;Whaley and Kibby, 1981). The results from studies of text disruption effects, timed text reading, and a variety of other paradigms also display a similar pattern (Allington and Strange, 1977;Biemiller, 1977Biemiller, -1978Ehrlich, 1981;Lovett, 1986;Nicholson, 1991;Schwartz and Stanovich, 1981;Stanovich, Cunningham, and Feeman, 1984;Strange, 1979).…”
Section: The Role Of Context In Word Recognitionmentioning
confidence: 75%
“…For example, studies of oral reading errors (Allington & Fleming, 1978;Batey & Sonnenschein, 1981;Biemiller, 1970Biemiller, , 1979Cohen, 1974Cohen, -1975Coomber, 1972;Juel, 1980;Lesgold & Resnick, 1982;Perfetti & Roth, 1981;Richardson, DiBenedetto, & Adler, 1982;Weber, 1970;Whaley & Kibby, 1981), timed text reading (Allington, 1978;Biemiller, 1977Biemiller, -1978Doehring, 1976), text disruption manipulations (Allington & Strange, 1977;Ehrlich, 1981;Schwartz & Stanovich, 1981;Siler, 1973Siler, -1974Strange, 1979), single-word priming (Schvaneveldt, Ackerman, & Semlear, 1977;Simpson, Lorsbach, & Whitehouse, 1983), and paragraph priming (Perfetti, Goldman, & Hogaboam, 1979;Schwantes, 1981Schwantes, , 1982). One of the most important is that Smith's developmental hypothesis regarding context use at the word level is falsified.…”
Section: Discussionmentioning
confidence: 99%
“…We expected to find reading time differences for the two groups of readers, given that several studies found that less skilled readers rely more on context for word identification than do more skilled readers (Perfetti & Lesgold, 1979;Schwartz & Stanovich, 1981;Stanovich, 1984). Although the interactive-compensatory model proposed that less skilled readers rely on context more, the effectiveness of these compensatory word identification processes is still an open question.…”
Section: Methodsmentioning
confidence: 98%